Water, water, but not everywhere: analysis of shrinking water bodies using open access satellite data. Issue 4 (19th May 2021) - Mahajan, Sachit; Martinez, Jenny
ABSTRACT: The importance of water cannot be overstated. Not only it is essential for life, it is a vital resource for sustainable development. Water resource management is pivotal to ensure water security and sustainability. Having such water monitoring resources is challenging, especially in less developed countries that have limited resources. With the advancement in technology and availability of open-access satellite data, there are opportunities to reinforce the abilities of researchers and decision-makers to monitor and identify changes in water resources. In this work, we describe an easy to implement workflow for estimation of surface area of waterbodies using open-access data from Sentinel-2 satellites. The method uses Normalized Difference Water Index (NDWI) for surface water detection that is used to estimate the surface area of the waterbody and analyse changes over a period of time. We develop four case studies based on waterbodies in Spain, Morocco, and India to highlight how satellite imaging can effectively help in estimating and visualizing the changes in water surface area. Temperature and rainfall data are analysed to understand the impact of climate change on water resources due to increase in temperature and changes in precipitation patterns. The proposed method is validated by testing it on four additional lakes and comparing the results with publicly available data. We show how open-access satellite data can potentially be used for regular monitoring of waterbodies as well as filling the knowledge gap to assist in decision making at both local and regional levels.